Indonesia's Decentralization After Crisis - Ma, Jun; Hofman, Bert (World Bank, Washington, DC, 2012)
In 1999, the Indonesian Parliament adopted two laws requiring that drastic decentralization measures be implemented in fiscal 2001 in a "big bang" fashion. Several lessons can be drawn from Indonesia's experience. 1) Ideally, decentralization should be managed so that the devolution of fiscal resources occurs in line with the devolution of spending. In reality, politics determines the devolution of resources, often with little regard for spending responsibilities. 2) Spending responsibilities can be devolved to a level of government in line with its administrative capacities. 3) Every effort should be made to avoid delays in establishing regulations that detail the responsibilities of various levels of government. 4) Local governments should be assigned one or a few substantive taxes over which they have some rate of autonomy, to ensure local accountability and fiscal discipline.